Pembinaan pola pengembangan program kerja Forum Silaturahim Mahasiswa Muslim (FORSIM) - Sri Widaningsih; Muhamad Yusuf Nursyamsi (Abdimas Siliwangi, 2023)
The Muslim Student Gathering Forum (FORSIM) as an Islamic-based student organization in the future must continue to progress and develop in a better direction and follow the demands and expectations of the Islamic student movement which is progressive and able to be competitive. The main goal is that each friendship forum can create a work development program pattern that is following the demands and expectations of the era to be faced, the method of implementing this community service activity uses the "community development practice" workflow. The results of the coaching carried out are that Forsim has a work program that is not only based on Islam but can be varied, and the scoop work program continues to be developed according to needs and work programs. The conclusion from the whole series of services is that the pattern of coaching in the development of the Forsim work program is carried out in a systematic and structured manner in 4 main frameworks, namely needs analysis and setting priority scales, planning, and the coaching process, then coaching is closed with a review as well as evaluation, finally financing and program approval Work. The work program developed is a holistic work program that includes; spiritual, aesthetic, social, physical, and intellectual